Nitrogen immobilization may reduce invasibility of nutrient enriched plant community invaded by Phragmites australis - Uddin, Md Nazim (Sci Rep, 2020)
Nutrient enrichment, particularly nitrogen, is an important determinant of plant community productivity, diversity and invasibility in a wetland ecosystem. It may contribute to increasing colonization and dominance of invasive species, such as Phragmites australis, especially during wetland restoration. Providing native species a competitive advantage over invasive species, manipulating soil nutrients (nitrogen) may be an effective strategy to control the invasive species and that management tool is essential to restore the degraded ecosystems. Therefore, we examined competition between Phragmites australis and Melaleuca ericifolia in a greenhouse setting with activated carbon (AC) treatments, followed by cutting of Phragmites shoots in nutrient-rich soils. Additionally, we evaluated the effect of AC on plant-free microcosms in the laboratory, to differentiate direct effects of AC on soil microbial functions from indirect effects. Overall, the objective was to test whether lowering nitrogen might be an effective approach for reducing Phragmites invasion in the wetland. The AC reduced Phragmites total biomass more significantly in repeated cut regime (57%) of Phragmites shoots compared to uncut regime (39%). Conversely, it increased Melaleuca total biomass by 41% and 68% in uncut and repeated cut regimes, respectively. Additionally, AC decreased more total nitrogen in above-ground biomass (41 to 55%) and non-structural carbohydrate in rhizome (21 to 65%) of Phragmites, and less total nitrogen reduction in above-ground biomass (25 to 24%) of Melaleuca in repeated cut compared to uncut regime. The significant negative correlation between Phragmites and Melaleuca total biomass was observed, and noticed that Phragmites acquired less biomass comparatively than Melaleuca in AC-untreated versus AC-treated pots across the cutting frequency. AC also caused significant changes to microbial community functions across Phragmites populations, namely nitrogen mineralization, nitrification, nitrogen microbial biomass and dehydrogenase activity (P ≤ 0.05) that may potentially explain changes in plant growth competition between Phragmites and Melaleuca. The overall effects on plant growth, however, may be partially microbially mediated, which was demonstrated through soil microbial functions. Results support the idea that reducing community vulnerability to invasion through nutrient (nitrogen) manipulations by AC with reducing biomass of invasive species may provide an effective strategy for invasive species management and ecosystem restoration.